2014
DOI: 10.1039/c4tc00454j
|View full text |Cite
|
Sign up to set email alerts
|

Selective n-type doping in graphene via the aluminium nanoparticle decoration approach

Abstract: A simple and effective technique is presented to left shift the Dirac point of graphene transistors to induce n-type doping via the thermal decoration of Al nanoparticles. The versatility of this approach is illustrated by the fabrication of air-stable n-type doping in graphene devices with the improved on/off current ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(49 reference statements)
5
22
0
Order By: Relevance
“…iv) For all the metals investigated, including Au and Ag, the doping also depends on nanostructuring, since nanoparticles can have a WF lower than the corresponding bulk, and, as shown for Au, the doping can shift from p-type for thin films to n-type with decreasing the size of Au nanoparticles. 19 This change acts as a driving force for the transfer of electron from Al to graphene, which is n-doped more efficiently. v) Unintentional oxidation of the metal can also dramatically alter the WF M , as seen for Ag and Cu (see Fig.…”
Section: Characterizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…iv) For all the metals investigated, including Au and Ag, the doping also depends on nanostructuring, since nanoparticles can have a WF lower than the corresponding bulk, and, as shown for Au, the doping can shift from p-type for thin films to n-type with decreasing the size of Au nanoparticles. 19 This change acts as a driving force for the transfer of electron from Al to graphene, which is n-doped more efficiently. v) Unintentional oxidation of the metal can also dramatically alter the WF M , as seen for Ag and Cu (see Fig.…”
Section: Characterizationsmentioning
confidence: 99%
“…Understanding the metal-graphene interaction based on charge transfer from/to a metal to/from graphene layer is both fundamentally and technologically relevant for a number of reasons: (i) metal-graphene interactions regulate the chemical vapor deposition (CVD) of graphene on transition metals; 1 (ii) a graphene-metal heterojunction is an essential element in graphene-based devices, such as gas sensors, supercapacitors, printed electronics and photodetectors; (iii) in graphene electronics, the metal-graphene contact resistance limits the on-current of graphene field-effect transistors (FETs), while, in graphene optoelectronics a strong band bending in the vicinity of the metal-graphene junction can lead to efficient photocurrent; 2 (iv) metal nanoparticles (NPs), mainly gold (Au) and silver (Ag), have been used to both tune the visible spectrum and enhance absorption of graphene through localized surface plasmon resonance (LSPR) 3 for building new electrocatalysts for fuel cells; 4 (v) graphene-metal (Au, Ag, Pt and Pd) NPs have been synthesized using graphene oxide sheets as a precursor in solution approaches [5][6] to obtain nanocomposites for sensing and catalysis; 7 (vi) ultrathin metal layers and nanoparticles have been investigated both theoretically, [8][9][10][11] and experimentally [12][13][14][15][16][17][18][19] to modulate the work function (WF) of graphene by metal doping. Therefore, the WF of both graphene and the metal comprising a hybrid functional platform is one of the most important properties affected by the charge at the metal/graphene interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that chemical doping with HNO 3 as well FeCl 3 makes graphene film strongly p-type. 4,8 However, doping with ZnMg, 9 or via the aluminium nanoparticle decoration approach 10 and with hydrazine monohydrate 11 makes it n-type. Epitaxial graphene on silicon carbide has been found naturally n-doped.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Recently, it has been theoretically predicted that a metal layer adsorbed on graphene can induce p-or n-type doping with various carrier concentration depending on the work function difference between the metal and graphene, as well as their equilibrium separation. [20][21][22][23] However, it is difficult to control graphene-metal equilibrium separation by this metal layer deposition because a slight variation in deposition thickness significantly changes the surface morphology of the metal layer. [20][21][22][23] However, it is difficult to control graphene-metal equilibrium separation by this metal layer deposition because a slight variation in deposition thickness significantly changes the surface morphology of the metal layer.…”
Section: Introductionmentioning
confidence: 99%